Efektivitas Bahan Ajar Fisika Berbasis Inquiry dengan Pendekatan CTL untuk Meningkatkan Berpikir Kreatif Peserta Didik - Cahyati, Mona Trisna; Yohandri, Yohandri (Universitas Negeri Padang, 2021)
Learning based on the 2013 curriculum is oriented towards students to be active and able to find their own material so that students are trained in developing the knowledge they have and are able to improve students' creative thinking skills. The fact found that the learning carried out was not optimal. One of the contributing factors is that the teaching materials applied in the learning process are not in accordance with the needs and characteristics of students. The purpose of this study was to produce physics teaching materials based on the inquiry based learning model with the CTL approach to improve students' creative thinking with effective criteria. This type of research is research and development. Research and development is a research method used to produce certain products and test the effectiveness of these products. The research design used was a pretest-posttest control group design. The object of the study was inquiry based learning materials with the CTL approach to improve students' creative thinking. The instrument used was the effectiveness test sheet. Based on the data analysis, it was concluded that physics teaching materials based on the inquiry-based learning model with the CTL approach to improve creative thinking were developed effectively in physics learning. This can be seen from the aspects of knowledge and skills that have increased after using physics teaching materials.